A new replacement name in Lampetis Dejean, 1833 (Coleoptera: Buprestidae) - Bellamy, C. L. (Zootaxa, 2008)
In the final stages of checking the nearly 3,500 manuscript pages of a new world catalogue of jewel beetles (Bellamy, in prep.), I stumbled across what is perhaps the last unresolved case of homonymy in the family Buprestidae. This note is provided to correct this now with the proposal of a replacement name.